Strengthening Visceral Leishmaniasis Diagnosis Capacity to Improve Access to Care in Kenya: The Example of Marsabit County - de Souza, Dziedzom K.; Picado, Albert; Bessell, Paul R.; Liban, Abduba; Wachira, Davis; Mwiti, Daniel; Matendechero, Sultani H.; Bosch, Mercedes; Ndung’u, Joseph M.; Cruz, Israel (Frontiers in Tropical Diseases, 2022)
Background Visceral leishmaniasis (VL), also known as kala-azar, is a neglected tropical disease (NTD) that is fatal if not treated early. The WHO targets the elimination of VL as a public health problem in its 2030 NTD road map. However, improving access to VL diagnosis and treatment remains a major challenge in many VL-endemic countries. Kenya is endemic for VL and is among the top 6 high-disease burden countries in the world. Methods FIND, through its activities in improving the diagnosis of VL and supporting the elimination of the disease in Kenya, has worked with various county ministries of health (MOH) and central MOH over the last couple of years. FIND’s activities in Marsabit county started in 2018. In this work, we present the implementation of activities and the impacts in Marsabit county. We reviewed the data for 2017 and 2019 outbreaks (before and after the implementation of FIND’s activities) and assessed the importance of improving access and community sensitization to VL diagnosis. We assessed the contribution of each facility to the total distance traveled from a perspective of location optimization. Results There was a sharp increase in the number of people tested in the 2017 outbreak compared to the 2019 outbreak. In 2017, 437 people were tested compared to 2,338 in 2019. The county reported 234 and 688 VL cases in 2017 and 2019, respectively. The data revealed a shift in the demographic structures of cases toward the younger population (mean age in 2017 was 17.6 years and 15.3 years in 2019), with more female cases reported in 2019 compared to 2017. In 2017, 44.4% were 10 years of age or under. In 2019, the proportion 10 years or below was 52.2%. The addition of two new diagnosis facilities in 2018 resulted in a decrease in the distance traveled by confirmed VL cases from 28.1 km in 2017 to 10.8 km in 2019. Assessing the impact of facility placement indicated the most optimal facilities to provide VL diagnostic services and minimize the distance traveled by patients. Adding new facilities reduces the travel distance until a point where the addition of a new facility provides no additional impact. Conclusion The results from this study indicate the need to carefully consider the placement of health facilities in improving access to VL diagnosis and treatment and could serve as an investment case in deciding when to stop adding new facilities in a particular setting. Extending the activities in Kenya to other VL-endemic countries in East Africa will contribute significantly toward the elimination of the disease, addressing the needs of marginalized populations and leaving no one behind.